Chasing among older-aged gamblers: the role of mentalizing and psychological distress - Ciccarelli, Maria; Pizzini, Barbara; Cosenza, Marina; D’Olimpio, Francesca; Griffiths, Mark D.; Nigro, Giovanna (Frontiers in Psychiatry, 2024)
BackgroundDespite the increasing proportion of older-aged individuals suffering from problematic gambling, research on gambling among this specific age cohort is still in its infancy. Chasing is a pathognomonic feature of disordered gambling and is considered one of the key risk factors in the transition from recreational to disordered gambling. Despite the increased research on chasing over the past decade, no previous study has ever examined the psychological determinants of chasing behavior among old-aged gamblers. Given the importance of chasing in facilitating and maintaining problem gambling, and the paucity of research examining gambling among older individuals, the present study is the first to empirically investigate the joint role of chasing behavior, negative affectivity, and mentalizing among older-aged gamblers.MethodsThe sample comprised 116 older-aged gamblers who were administered the South Oaks Gambling Screen (SOGS), the Depression Anxiety Stress Scale (DASS-21) and the Reflective Functioning Questionnaire (RFQ-8) to assess gambling severity, psychological distress, and mentalizing, respectively. Participants also performed the ChasIT, a computerized task that assesses chasing behavior, in which participants were randomly assigned to three different experimental conditions: loss, control, and win.ResultsNo effect of the experimental conditions of ChasIT on chasing behavior was observed. Regression analyses indicated that heightened levels of gambling severity and lower levels of certainty about mental states (i.e., hypermentalizing) predicted both the decision to chase and chasing frequency. Along with problem gambling and hypermentalizing, chasing frequency was also predicted by high levels of depression.ConclusionsThe present study demonstrated the association between disordered gambling, depression, and hypermentalizing in chasing behavior among older-aged gamblers. The findings make an important contribution to providing insight regarding variables that are associated with chasing among older-aged gamblers, one of the least represented populations of gamblers in the literature. The results suggest that specific training on mentalizing abilities could help gamblers to reflect on their own behaviors in terms of mental states, rather than following the impulse to gamble in order to ameliorate poor mood.